Effect of lactoferrin on enamel characteristics of primary and permanent teeth: an in-vitro study - Nouran Samir Mohamed Atia; Reham Ahmed El-nemr; Asmaa Ali Emam Abo-Elsoud (BMC, 2023)
Abstract Background Lactoferrin, a glycoprotein naturally found in breast milk, is known for its bactericidal and antiviral properties, as well as its capacity to modulate the immune system; therefore, pediatricians routinely recommend it as dietary support. The objective of this study was to determine how lactoferrin oral suspension could affect the enamel surface characteristics of primary and permanent teeth. Methods This research was conducted on 40 unidentified extracted teeth, including primary and permanent teeth. Experimental teeth were free of cracks or enamel defects, as confirmed by careful examination using a dental operating microscope. The crowns were bisected into 80 specimens and assorted into two groups based on the type of dentition. Group DM included 40 specimens of second deciduous molars, while Group PM contained 40 samples of first premolars. Each of the DM and PM specimens was subsequently split based on the type of dispersion medium into two subgroups: a control subgroup (artificial saliva) and a test subgroup (lactoferrin suspension). The specimens were immersed in lactoferrin suspension for two minutes, then kept in artificial saliva for the rest of the 24 h for 30 successive days. This is a pioneering study about the effect of orally supplemented lactoferrin on teeth; therefore, we examined enamel hardness, ultra-morphology, and mineral contents. Results Our findings indicated a highly significant decrease (p < 0.01) in the microhardness of the lactoferrin subgroup in Group DM (second deciduous molars) and a significant reduction (p < 0.05) in the microhardness of the lactoferrin subgroup in Group PM (premolars). Calcium weight% was not statistically different (p > 0.05) compared with a significant decline (p < 0.05) in phosphorus weight% in lactoferrin subgroups in both DM and PM groups. The enamel surface of lactoferrin subgroups in both DM and PM groups was demineralized and porous, with the enamel of deciduous teeth being more affected by lactoferrin than permanent teeth. Conclusion Lactoferrin suspension decreased the microhardness of enamel and both calcium and phosphorus weight percentages. Both dentitions exhibited erosions in the enamel surface, with primary teeth being more affected than the permanent teeth.